ChemInform Abstract: Synthesis, Cyclization, and Evaluation of the Anticancer Activity Against HeLa S‐3 Cells of Ethyl 2‐Acetylamino‐3‐ethynylazulene‐1‐carboxylates. Issue 17 (4th April 2013) - Hyoudou, Marie; Nakagawa, Hajime; Gunji, Takahiro; Ito, Yoshino; Kawai, Yu; Ikeda, Reiko; Konakahara, Takeo; Abe, Noritaka
Abstract The iodination of azulene derivatives of type (I) or (VI) and some consecutive reactions are studied.